Bangladesh Financial Reporting Standard (BFRS) and Environmental Accounting: A Case Study of Listed Manufacturing Companies in Bangladesh - Biswas, Md Islam; Rahaman, Md Mustafizur (Journal of Business and Technology (Dhaka), 2013)
This paper examines whether Bangladesh Financial Reporting Standards (BFRS) can be used for monitoring environmental degradations. The paper critically examines the contemporary environmental accounting literature, and attempts to find a mandatory reporting mechanism in the context of accounting for a public good. It selects the relevant financial reporting standards and examines their strengths and weaknesses. Using qualitative and case-study research methods, the financial statements of 65 local manufacturing companies that are operating in an environmentally sensitive sector are studied. The study finds that the Global Reporting Initiatives (GRI) guidelines and the private sectors self-regulation are insufficient to monitor environmental disclosure. The paper proposes a mandated separate statement of environmental assets and liabilities. The elements of the proposed statement are discussed. DOI: http://dx.doi.org/10.3329/jbt.v6i2.14514 Journal of Business and Technology (Dhaka) VolVI, Issue02, (July-December, 2011) & VolVII, Issue-1 (January-June, 2012) pp.1-20